Medical error in theory and practice - a review of the most important issues - Elżbieta Alicja Puch; Monika Nowak-Jaroszyk; Ewelina Swora-Cwynar (Nofer Institute of Occupational Medicine, 2020)
In recent years, in Poland, despite the lack of an adverse medical events monitoring system, a sharp increase in the number of complaints to various medical and legal institutions, as well as court cases with a suspicion of a medical error, was found, based on the available reports and statistics, which poses a serious medical and legal. The aim of this study was to review the theoretical and practical issues of medical errors in the medico-legal context on the basis of the current legislation in Poland. This paper presents the conceptual scope and the evolution of terminology, starting from "error in the medical art/craft" up to the currently defined and used concept of "medical error." The problem of medical errors in medico-legal categories, according to Polish legal regulations and ethical standards in medicine, was also considered. Different classifications, as well as the causes and consequence of various medical errors, were analyzed. Based on current literature, Polish judicial decisions were reviewed, and some examples of legal rulings with respect to different categories of medical errors were presented. Given the ambiguity, both in conceptual and categorizing terms, with regard to adverse medical events: errors, negligence, malpractice and omission, it would be justified to adopt an unambiguous definition and classification. Such an arrangement would expand the possibilities of research in the field of etiology of medical errors, and more importantly, prepare such procedures that would maximally protect the patient, and allow the maximum reduction of the number of medical errors and any other adverse events. In addition, specifying the medical, legal and economic standards in medical units, and determining the scope of personal and institutional responsibility for undesirable medical events, would, in turn, improve the processing of claims made by patients or their families, as well as the activities of medical and legal institutions, including doctors appointed as court experts. Med Pr. 2020;71(5):613-30